2005
DOI: 10.1111/j.1365-2036.2005.02435.x
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety, depression and psychotropic medication use in patients with persistent upper and lower gastrointestinal symptoms

Abstract: Background: Limited information is available about anxiety, depression and psychotropic medication use in patients referred for gastrointestinal endoscopy. Aim: To determine anxiety and depression and its association with endoscopic findings in a representative sample of patients with persistent gastrointestinal symptoms prior to endoscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0
1

Year Published

2006
2006
2012
2012

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 23 publications
(33 reference statements)
0
14
0
1
Order By: Relevance
“…Moreover, our data also seem to be in line with the few data reported in patients affected by organic gastrointestinal diseases. In particular using hospital anxiety and depression scale (HADS) psychometric scale in a large cohort of patients, Van Kerkhoven et al (2) recently showed the presence of anxiety and depression in subjects referred to digestive endoscopy outpatient setting. In this study evaluating patients referred for lower gastrointestinal endoscopy, there were no differences in anxiety and depression between patients with functional disorders and those with organic causes for their symptoms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, our data also seem to be in line with the few data reported in patients affected by organic gastrointestinal diseases. In particular using hospital anxiety and depression scale (HADS) psychometric scale in a large cohort of patients, Van Kerkhoven et al (2) recently showed the presence of anxiety and depression in subjects referred to digestive endoscopy outpatient setting. In this study evaluating patients referred for lower gastrointestinal endoscopy, there were no differences in anxiety and depression between patients with functional disorders and those with organic causes for their symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Anxiety and depression represent a common feature in patients affected by gastrointestinal diseases (1,2). In some cases as in patients with functional gastrointestinal disorders, anxiety and depression are present particularly as a personality trait (3) and they seem to play a main role in the genesis and/or the perception of symptoms (1).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have tended to emphasize that irritable bowel syndrome (IBS) patients are significantly more anxious and depressed than healthy controls 3–6 and have a higher incidence of previous psychiatric disease 7, 8 . Although this is true, anxiety is a major driver for any consultation 9, 10 and hence it is perhaps not surprising that anxiety is not a useful aid in differential diagnosis as it fails to distinguish clearly IBS patients from patients with other gastrointestinal (GI) diseases such as colon cancer, coeliac disease, peptic ulcer, 11 inflammatory bowel disease 12 or indeed most general medical conditions 13, 14 …”
Section: Introductionmentioning
confidence: 99%
“…However, a majority of dyspeptic patients seeking medical attention are managed in primary care. Patients referred to secondary care are known to have more severe dyspeptic symptoms and symptoms of psychological disturbances 18, 19 . For this reason, results from secondary care studies suggesting an association between psychological factors and dyspepsia cannot automatically be applied to the primary care population.…”
Section: Introductionmentioning
confidence: 99%